Effects of Mexican Ganoderma lucidum extracts on liver, kidney, and the gut microbiota of Wistar rats: A repeated dose oral toxicity study - Meneses, María E.; Martínez-Carrera, Daniel; González-Ibáñez, Laura; Torres, Nimbe; Sánchez-Tapia, Mónica; Márquez-Mota, Claudia C.; Rendón, Gilmar; Mitzi, Vladimir; Morales, Alfredo; Tello-Salgado, Isaac; Tovar, Armando R. (PloS one, 2023)
Well-characterized and standardized extracts of a Mexican genotype of Ganoderma lucidum ( Gl ), a medicinal mushroom, cultivated on oak sawdust ( Gl -1) or oak sawdust plus acetylsalicylic acid ( Gl -2, ASA), have been shown to exert antioxidant, hypocholesterolemic, anti-inflammatory, prebiotic, and anticancer properties. However, toxicity analyses still need to be carried out. Different doses of these Gl -1 or Gl -2 extracts were administered to Wistar rats for 14 days in a repeated dose oral toxicity study. We assessed the external clinical signs, biochemical parameters, liver and kidney tissues, injury and inflammation biomarkers, gene expression, inflammatory responses, proinflammatory mediators, and gut microbiota. Gl extracts had no significant adverse, toxic or harmful effects on male and female rats compared to the control groups. No injury or dysfunction were recorded in the kidney or liver, as there were no significant abnormal variations in organ weight, tissue histopathology, serum biochemical parameters (C-reactive protein, creatinine, urea, glucose, ALT and AST transaminases, TC, LDL-c, TG, HDL-c), urinary parameters (creatinine, urea nitrogen, albumin, the albumin-to-creatinine ratio, glucose), injury and inflammatory biomarkers (KIM-1/TIM-1, TLR4, and NF-кB protein expression; IL-1β, TNF-α and IL-6 gene expression), or the expression of genes linked to cholesterol metabolism (HMG-CoA, Srebp2, Ldlr). Gl -1 and Gl -2 extracts showed prebiotic effects on the gut microbiota of male and female Wistar rats. Bacterial diversity and relative bacterial abundance (BRA) increased, positively modulating the Firmicutes/Bacteroidetes ratio. The ASA (10 mM) added to the substrate used for mushroom cultivation changed properties and effects of the Gl -2 extract on Wistar rats. The no-observed-adverse-effect-level (NOAEL) was 1000 mg/kg body weight/day of Gl -1 or Gl -2 extracts. Clinical trials are recommended for further exploring the potential therapeutic applications of studied extracts.